Polarized image of a Schwarzschild black hole with a thin accretion disk as photon couples to Weyl tensor - Zelin Zhang (SpringerOpen, 2021)
Abstract We have studied polarized image of a Schwarzschild black hole with an equatorial thin accretion disk as photon couples to Weyl tensor. The birefringence of photon originating from the coupling affect the black hole shadow, the thin disk pattern and its luminosity distribution. We also analyze the observed polarized intensity in the sky plane. The observed polarized intensity in the bright region is stronger than that in the darker region. The stronger effect of the coupling on the observed polarized vector appears only in the bright region close to black hole. These features in the polarized image could help us to understand black hole shadow, the thin accretion disk and the coupling between photon and Weyl tensor.